The fourth term of the binomial expansion
can be calculated using the formula for (i+1)-th term of the binomial expansion:
![T_{i+1}=C_{10}^i\cdot e^{10-i}\cdot (2f)^i.](https://tex.z-dn.net/?f=T_%7Bi%2B1%7D%3DC_%7B10%7D%5Ei%5Ccdot%20e%5E%7B10-i%7D%5Ccdot%20%282f%29%5Ei.)
In order to find term
, determine that
![i+1=4\Rightarrow i=3.](https://tex.z-dn.net/?f=i%2B1%3D4%5CRightarrow%20i%3D3.)
Now
![T_4=C_{10}^3\cdot e^{10-3}\cdot (2f)^3=C_{10}^3\cdot e^7\cdot (2f)^3.](https://tex.z-dn.net/?f=T_4%3DC_%7B10%7D%5E3%5Ccdot%20e%5E%7B10-3%7D%5Ccdot%20%282f%29%5E3%3DC_%7B10%7D%5E3%5Ccdot%20e%5E7%5Ccdot%20%282f%29%5E3.)
Answer: correct choice is A
Answer:
No, Walden was not asking a statistical question because all the people living in the same house would give him the same answer to his question. So the question did not allow for multiple answers among the population that it was posed to.
Step-by-step explanation:
i did the test
Answer:
Step-by-step explanation:
The last three are irrational but I'm not sure about the first four.
-2 < n
![\leq](https://tex.z-dn.net/?f=%20%5Cleq%20)
3
This inequality basically says "-2 is less than n, which is less than or equal to 3".
Mark as brainliest if this helped! :)